IMPACT OF ROTOR REMOVAL ON STEAM TURBINE PERFORMANCE - Kosasih, Joey
This study used computational fluid dynamics (CFD) to analyze the reduction of steam turbine performance due to one-stage rotor removal. A steam turbine which consists of five impulse stages with dry steam as the working fluid are introduced as research model. Three cases that are compared and analyzed are operation with full rotor, operation without middle-stage rotor, and operation without last-stage rotor. The steam turbine is modelled using ExportPoints method in ANSYS BladeEditor. Numerical simulations are conducted using the software CFX. The validation process for two cases of rotor removal condition are completed by comparing several parameters with the result of full rotor simulation that is already validated by the actual data from the heat balance diagram of relevant steam turbine. Based on the simulation result, the power output which is produced by the steam turbine operating with full rotor condition has a value of 19.95 MW. Meanwhile, the steam turbine without one-stage rotor produces a fewer amount of power. In the operation without middle-stage rotor case, the power generated are 11.05% less, while in the operation without last-stage rotor case, there is 21.69% power reduction. In additional research concerning one-stage stator and rotor removal, the steam turbine shows a better performance with less power reduction due to components removal.